Fast food consumption frequency and prediabetes among young adults in makassar: A Cross-Sectional Study - Sitti Masita; Hasniati Haeruddin; Harbaeni Harbaeni; Syafira Rulmadani; Maria Kurnya Rante Kada (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Prediabetes is a critical intermediary metabolic condition that substantially increases the risk of type 2 diabetes mellitus and cardiovascular disease. Rapid urbanization and dietary transition in Indonesia have contributed to increased consumption of energy-dense fast food among young adults, potentially accelerating early metabolic dysregulation. This study aimed to determine the association between the frequency of fast-food consumption and prediabetes among young adults in an urban primary healthcare setting in Makassar, Indonesia. Research Methodology: An analytical cross-sectional study was conducted from August to September 2023 at Malimongan Baru Community Health Center. A total of 57 young adults aged 20–35 years were recruited using convenience sampling. Fast food consumption frequency was assessed using a structured Food Frequency Questionnaire. Prediabetes was defined as fasting blood glucose levels of 100–125 mg/dL. Descriptive statistics were performed, followed by bivariate analysis and multivariable logistic regression to estimate adjusted odds ratios (AOR) with 95% confidence intervals (CI). Statistical significance was set at α = 0.05. Results: 86.0% of participants reported high fast-food consumption, and 54.4% were classified as having prediabetes. In multivariable analysis, frequent fast-food consumption was independently associated with prediabetes (AOR = 2.03; 95% CI: 1.12–3.87; p = 0.021). Participants with BMI ≥25 kg/m² also had higher odds of prediabetes (AOR = 2.67; 95% CI: 1.18–6.02; p = 0.018). Conclusion: Frequent fast-food consumption is a significant behavioral determinant of prediabetes among urban young adults. Integrating dietary risk screening and nutrition counseling within primary healthcare services is essential to prevent early progression to type 2 diabetes.